SOIL HEALTH TRAINING AS THE IMPLEMENTATION OF THE SUSTAINABLE CORPORATE SOCIAL RESPONSIBILITY (CSR) PROGRAM PT. INPOLA MEKA ENERGI: PELATIHAN KESEHATAN TANAH SEBAGAI IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) BERKELANJUTAN PADA PT. INPOLA MEKA ENERGI - Halim Akbar; Sakral Hasby Puarada; Muhammad Authar ND; Riris Nadia Syafrilia Gurning (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
Soil health is an important aspect of agricultural sustainability because it encompasses the soil's physical, chemical, and biological functions. This service activity aims to increase farmer groups' understanding of  concepts, indicators, and simple methods for recognizing and evaluating soil health as part of the  implementation of PT. Inpola Meka Energi. The activity was held on May 9, 2025, in Lau Gunung Village, Tanah Pinem District, Dairi Regency, North Sumatra, using an educational-participatory  approach through the delivery of materials, discussions, introduction to tools, and field observations in the  cocoa plantation area. The material includes 12 soil health indicators grouped into physical, chemical, and  biological aspects, as well as evaluation stages: indicator observation, scoring, use of the Soil Health Card, determination of the Soil Health Index (IKT), identification of limiting factors, and alternative  improvements. The results of the activity demonstrated the implementation of the knowledge transfer  process and field learning, with participants directly recognizing soil conditions. This activity is a form of  CSR based on community capacity building to support sustainable land management.